Vysetrení mutacního statutu genu KRAS jako soucást algoritmu lécby metastatického kolorektálního karcinomu - Dubská, Lenka; Vyskocilová, Martina; Nenutil, Rudolf; Valík, Dalibor; Knoflícková, Dana; Fabian, Pavel; Kocáková, Ilona; Demlová, Regina; Beránek, Martin; Drastíková, Monika; Vosmiková, Hana; Bóday, Arpád; et al. (Casopis lekaru ceskych, 2011)
Targeted therapy has become an integral part of treatment procedures of malignant tumors. Colorectal carcinomas are frequently targeted with monoclonal anti-EGFR antibodies (cetuximab and panitumumab). Activating somatic mutations in codons 12 and 13 of the exon 2 of KRAS gene are considered negative predictive factors of response to anti-EGFR therapy in patients with metastatic colorectal cancer. In the Czech Republic, evaluation of mutational status of KRAS gene is performed in several referral laboratories. In 2009, these laboratories performed 2580 tests of the KRAS mutational status--out of these, 60.2% cases reported non-mutated, wild-type KRAS. In one of the referral laboratories, we demonstrate the logistics of KRAS testing procedure. Stratification of patients with metastatic colorectal tumors based on their KRAS mutational status has evolved to a standard procedure. Laboratories performing these methods shall therefore adhere to the recommendations of the professional and accredited societies.
Keywords: monoklonální protilátky; Colorectal Neoplasms; mutace; protinádorové látky; panitumumab; Antibodies, Monoclonal; Genes, ras; Humans; lidé; Antibodies, Monoclonal, Humanized; Mutation; kolorektální nádory; Antineoplastic Agents; geny ras; cetuximab; Panitumumab; humanizované monoklonální protilátky; Cetuximab